The African dimension in Libyan foreign policy 1969-2002 - (:unkn) unknown (My University, 2012)
The aim of this thesis is to study the Libyan foreign policy in Africa from 1969 to 2002. The foreign Libyan political decision had been influence by many political, ideological and international directions. The petroleum had allowed to Libyan politics to exercise an important role by using important amount of money coming from the petroleum revenue. The latter had brought financial and economic assistance, which bring Libyan assistance policy essential in many African countries.After the end of the cold war and the world domination by the American politics, Libya had been accuse in the Lockerbie affaires and had been sanction by the United Nations. The political sanctions and the economic embargo conduct Libya to change its foreign policy and abandon the struggle against the presence of Americans and Israelis in Africa, as well as to adopt a foreign policy in the trends of Occidental interest
Keywords: African Research